2022
DOI: 10.3389/fcvm.2022.839483
|View full text |Cite
|
Sign up to set email alerts
|

Restructuring the Heart From Failure to Success: Role of Structural Interventions in the Realm of Heart Failure

Abstract: Heart failure through the spectrum of reduced (HFrEF), mid-range (or mildly reduced or HFmEF), and preserved ejection fraction (HFpEF), continues to plague patients' quality of life through recurrent admissions and high mortality rates. Despite tremendous innovation in medical therapy, patients continue to experience refractory congestive symptoms due to adverse left ventricular remodeling, significant functional mitral regurgitation (FMR), and right-sided failure symptoms due to significant functional tricusp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…The device, a Pivot-TR system, has the 3D leaflet as a coaptation enhancer. Several spacer-based devices have been developed for the treatment of tricuspid regurgitation (TR), including the Edwards Forma [ 4 ], Coramaze [ 13 ], and Croiduo valve [ 14 ]. A key distinction between these devices and the Pivot-TR system lies in their requirement for a coaxial spacer orientation, as opposed to the vertical orientation of the Pivot-TR.…”
Section: Discussionmentioning
confidence: 99%
“…The device, a Pivot-TR system, has the 3D leaflet as a coaptation enhancer. Several spacer-based devices have been developed for the treatment of tricuspid regurgitation (TR), including the Edwards Forma [ 4 ], Coramaze [ 13 ], and Croiduo valve [ 14 ]. A key distinction between these devices and the Pivot-TR system lies in their requirement for a coaxial spacer orientation, as opposed to the vertical orientation of the Pivot-TR.…”
Section: Discussionmentioning
confidence: 99%
“…The device is delivered via an 18Fr steerable catheter via femoral venous access. The Tripair device is currently in pre-clinical testing ( 91 ).…”
Section: Miscellaneous Therapiesmentioning
confidence: 99%
“…Heart failure with reduced ejection fraction results in progressive deleterious left ventricular remodeling leading to increased end-diastolic volumes, myocardial stress, functional mitral regurgitation, and worsening heart failure symptoms [53]. Early surgical techniques of left ventricular geometry restoration have been met with mixed results; however, this adverse remodeling of the left ventricular cavity has recently generated renewed interest as a target of percutaneous left ventricular restoration devices [54].…”
Section: Ventricular Restorative Devicesmentioning
confidence: 99%
“…Results have been mixed across the PARACHUTE trials and more research is necessary to determine the safety and outcomes associated with these devices; a detailed review of the Parachute device can be found from Dhakal and Oliveira [55]. This Parachute device is not currently in use [53].…”
Section: Parachute Devicementioning
confidence: 99%
See 1 more Smart Citation